The relationship between students' motivation and their perceived amount of basic psychological need satisfaction – a differentiated investigation of students' quality of motivation regarding biology. Issue 17 (21st November 2020) - Kaiser, L.-M.; Großmann, N.; Wilde, M.
ABSTRACT: As biology education is obliged to enable students to acquire scientific literacy, long-lasting and sustainable learning is required. According to self-determination theory, such learning is based on self-determined motivation. Therefore, motivating students is a key issue of biology teaching. The present study investigated whether students' quality of motivation depends on the extent to which their basic needs are satisfied. Initial studies confirmed a positive impact on biology learning in terms of perceived autonomy, competence, and relatedness. However, these studies (1) do not consider all three basic needs, (2) nor do they distinguish between all motivational regulation styles separately. A more fine-grained investigation is required. Thus, a cross-sectional study with 738 students was conducted. Structural analyses showed differing effects of the students' perceived autonomy, competence, and relatedness on their motivational regulation. The perception of autonomy and competence were important predictors of intrinsic and identified regulation. However, while intrinsic regulation required mainly the perception of autonomy, identified regulation depended mainly on competence. Perceived relatedness had no predictive power. When it came to controlled regulations, only the perceived relatedness was a negative predictor of students' introjected regulation. Regarding external regulation, neither perceived autonomy and competence nor relatedness were negative predictors.